War and Genocide in South Sudan - Pinaud, Clémence, 1985- (Book collections on Project MUSE., 2021)
"This book explores the relationship between predatory wealth accumulation, state formation, and extreme ethnic group entitlement with genocidal potential in South Sudan. It traces the rise of a predatory state during the second civil war (1983-2005) and its transformation into a violent Dinka ethnocracy after independence that waged genocide against non-Dinka civilians in the third civil war (2013-)"--